EXPLORING STUDENTS' PROBLEMSIN ACCOMPLISHING WRITING TASK 1 OF IELTS ACADEMIC MODULE: a case study at an EAP course in a Language Centre in Bandung, West Java - Susana, Ani (2012)
This study was undertaken to explore students' problems in accomplishing Writing Task 1 of IELTS Academic Module, in terms of IELTS Academic Module assessment criteria of Writing Task 1 (task achievement, coherence and cohesion, lexical resource, and grammatical range and accuracy). This study also tried to find solutions to help the students overcome the problems. The present study was largely qualitative. The participants of the study were nine students and one teacher at an EAP course in a university language center. In order to gain valid data, the study employed triangulation of data collection methods of classroom observation, documentation of students' texts, and interviews. The data were analyzed qualitatively with the help of some quantitative calculation. First, the data from students' texts were analyzed based on the assessment criteria of Writing Task 1 of IELTS Academic Module to identify the students' problems. Second, the data from classroom observations were summarized and analyzed qualitatively. Next, the data from interviews were transcribed and classified. Finally, the data from the three sources were synthesized to answer the research questions. It was found that the students had most problems with the lexical resource. They were not able to use varied words/good vocabulary, to paraphrase the information given in the task, to choose right word forms, and to use correct spelling and punctuations in their writing. On the other hand, they had fewest problems with the task achievement. Summarizing significant features and writing at least 150 words were the only problems faced by the students. In terms of coherence and cohesion, the students had problems with spelling and making complex sentences but they did not encounter any problem with interpreting the task, using right pronoun, making introduction paragraph and developing body paragraphs. Related to the grammatical range and accuracy, the students mostly had problem with using right adjective/noun/verb/adverb to describe information. They also encountered difficulty in using active and passive voice, in using prepositions in sentences, and in making different types of sentences. Both the teacher and the students did several ways to solve the students' problems. Teacher's self-initiated solutions in the forms of written and spoken feedback, student's self-initiated solutions in the forms of editing and proof-reading, and peer-feedback in the forms of peer-correction and peer-evaluation were employed to cope with the problems. The results of this study are expected to provide information on the actual condition of EAP course focused on IELTS training. They may become useful sources for EAP or/and English Writing teacher to improve their teaching and to give input for other researchers who intend to conduct research in the same field.